Positron Emission Tomography (PET) Imaging of Multiple Myeloma in a Post-Treatment Setting - Giulia Ferrarazzo; Silvia Chiola; Selene Capitanio; Maria Isabella Donegani; Alberto Miceli; Stefano Raffa; Alberto Stefano Tagliafico; Silvia Morbelli; Matteo Bauckneht (Diagnostics, 2021)
2-deoxy-2-[18F]fluoro-D-glucose (FDG) positron emission tomography/computed tomography (FDG PET/CT) has an established clinical value in the diagnosis and initial staging of multiple myeloma (MM). In the last ten years, a vast body of literature has shown that this tool can also be of high relevance for monitoring therapy responses, making it the recommended imaging approach in this field. Starting from the strengths and weaknesses of radiological imaging in MM, the present review aims to analyze FDG PET/CT’s current clinical value focusing on therapy response assessment and objective interpretation criteria for therapy monitoring. Given the potential occurrence of patients with MM showing non-FDG-avid bone disease, new opportunities can be provided by non-FDG PET tracers. Accordingly, the potential role of non-FDG PET tracers in this setting has also been discussed.